Prospects for the detection of fast radio bursts with the Murchison Widefield Array - Trott, Cathryn; Tingay, Steven; Wayth, Randall (Institute of Physics Publishing, 2013)
Fast radio bursts (FRBs) are short timescale («1 s) astrophysical radio signals, presumed to be a signature of cataclysmic events of extragalactic origin. The discovery of six high-redshift events at ~1400 MHz from the Parkes radio telescope suggests that FRBs may occur at a high rate across the sky. The Murchison Widefield Array (MWA) operates at low radio frequencies (80-300 MHz) and is expected to detect FRBs due to its large collecting area (~2500 m2) and wide field-of-view (FOV, ~ 1000 deg2 at v = 200 MHz). We compute the expected number of FRB detections for the MWA assuming a source population consistent with the reported detections. Our formalism properly accounts for the frequency-dependence of the antenna primary beam, the MWA system temperature, and unknown spectral index of the source population, for three modes of FRB detection: coherent; incoherent; and fast imaging. We find that the MWA's sensitivity and large FOV combine to provide the expectation of multiple detectable events per week in all modes, potentially making it an excellent high time resolution science instrument. Deviations of the expected number of detections from actual results will provide a strong constraint on the assumptions made for the underlying source population and intervening plasma distribution.